Construction of the fundamental solution of a class of degenerate parabolic equations of high order - Malytska, H.P.; Burtnyak, I.V. (Carpathian Mathematical Publications, 2020)
In the article, using the modified Levy method, a Green's function for a class of ultraparabolic equations of high order with an arbitrary number of parabolic degeneration groups is constructed. The modified Levy method is developed for high-order Kolmogorov equations with coefficients depending on all variables, while the frozen point, which is a parametrix, is chosen so that an exponential estimate of the fundamental solution and its derivatives is conveniently used.